Factors Associated with Hypertension in Menopouse Women - Ridwan, M .; Fibrila, Firda; Fathunnikmah, Fathunnikmah (JURNAL PROTEKSI KESEHATAN, 2024)
The results of a pre-survey at the Mulyojati Metro City Health Center in 2022 out of 460 menopausal women there were 264 (57%) menopausal women who experienced hypertension. The purpose of the study was to determine the factors associated with the incidence of hypertension in menopausal women, using a quantitative analytic survey with a case control design. The population in this study were all postmenopausal women at the Mulyojati Health Center in Metro City who met the inclusion and exclusion criteria with a sample of 32 people and 32 controls (1: 1 ratio), so that the total sample was 64 people. Using Simple Random Sampling technique and data analysis using chi-square test. The results of the study of 32 respondents, as many as 68.8% (22 people) suffered from hypertension and were at risk of age with statistical test results obtained p-value = 0.045 (≤α 0.05), as many as 34.4% (11 people) who suffered from hypertension had experienced menopause with statistical test results obtained = 0.012 (≤α 0.05), as many as 21, 9% (7 people) who suffer from hypertension are highly educated with statistical test results obtained p-value = 0.064 (> α 0.05), as many as 68.8% (22 people) who suffer from hypertension have a hereditary history of hypertension with statistical test results obtained p-value = 0.003 (≤α 0.05) and as many as 40.6% (13 people) suffer from hypertension. Hypertension and obesity with statistical test results obtained p-value = 0.005 (≤α 0.05). In conclusion, of the 5 (five) independent variables studied, there are 4 (four) variables that are proven to have an association with the incidence of hypertension in menopausal women.